2018
DOI: 10.1063/1.5010855
|View full text |Cite
|
Sign up to set email alerts
|

Super-low-frequency wireless power transfer with lightweight coils for passing through a stainless steel plate

Abstract: To achieve wireless power transfer (WPT) through a stainless-steel plate, a super-low frequency (SLF) was used as a resonance frequency. In our previous study of SLF-WPT, heavy coils were prepared. In this study, we designed lightweight coils using a WPT simulator that we developed previously. As a result, the weight was reduced to 1.69 kg from 11.9 kg, the previous coil weight. At a resonance frequency of 400 Hz, the transmission efficiency and output power of advanced SLF-WPT reached 91% and 426 W, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…However, such systems often utilise metallic components that make induction difficult to achieve. Studies have shown that super-low-frequency induction can be utilised to reduce the dissipation effects of metal surfaces [130], increasing the use cases for this type of technology by expanding operating environments.…”
Section: Sources Of Energymentioning
confidence: 99%
“…However, such systems often utilise metallic components that make induction difficult to achieve. Studies have shown that super-low-frequency induction can be utilised to reduce the dissipation effects of metal surfaces [130], increasing the use cases for this type of technology by expanding operating environments.…”
Section: Sources Of Energymentioning
confidence: 99%
“…However, existing works are mainly based on experiments and there is a lack of analytical model to provide more insightful understanding of the magnetic field propagation through metal walls. In these experiments, the carrier frequency varies from 50 Hz to several MHz and the coil profile are also very different [6], [14]. It is not clear what is the optimal configuration, i.e., carrier frequency, coil number of turns, coil size, and coil position.…”
Section: Introductionmentioning
confidence: 95%
“…In a practical environment, there are probably some metal materials around the coils. The eddy current loss that will occur in these materials is proportional to the square of the frequency (7) . We think a low frequency range should be used to reduce heat generation in nearby metal materials.…”
Section: Introductionmentioning
confidence: 99%